Republic of Belarus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper describes labor market trends in Belarus and the role of labor market institutions in the outcome. The paper examines the current status of the tax system in Belarus and assesses recent efforts to reform it. It argues that the current tax system in Belarus is distortionary, and that it weakens the competitiveness of the economy. The paper also provides preliminary estimates of the pass-through from the nominal exchange rate (for the U.S. dollar and the ruble) to inflation in Belarus.